2014
DOI: 10.1016/j.jaac.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress and Trauma and Enhanced Limbic Activation to Emotionally Valenced Faces in Depressed and Healthy Children

Abstract: Objective Previous studies have examined the relationships between structural brain characteristics and early life stress in adults. However, there is limited evidence for functional brain variation associated with early life stress in children. We hypothesized that early life stress and trauma would be associated with increased functional brain activation to negative emotional faces in children with and without a history of depression. Method Psychiatric diagnosis and life events in children (starting at ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 89 publications
4
44
1
Order By: Relevance
“…20,37,[40][41][42] Functional studies are most consistent; lower childhood SES and risky family environments are associated with greater or less-regulated amygdala activation during emotion processing tasks. 47,49,51,52 Chronic stress appears to be a factor in the relationship between childhood poverty and amygdala activity, 47 and studies have highlighted the role of parent functioning. For example, threats to the parent-child bond, including maternal depression and insecure infant attachment, have been associated with larger amygdalae in childhood and young adulthood, 48,50 as well as higher amygdalahippocampal volume ratios, a risk factor for emotional dysregulation.…”
Section: Amygdala: Fear and Emotional Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…20,37,[40][41][42] Functional studies are most consistent; lower childhood SES and risky family environments are associated with greater or less-regulated amygdala activation during emotion processing tasks. 47,49,51,52 Chronic stress appears to be a factor in the relationship between childhood poverty and amygdala activity, 47 and studies have highlighted the role of parent functioning. For example, threats to the parent-child bond, including maternal depression and insecure infant attachment, have been associated with larger amygdalae in childhood and young adulthood, 48,50 as well as higher amygdalahippocampal volume ratios, a risk factor for emotional dysregulation.…”
Section: Amygdala: Fear and Emotional Processingmentioning
confidence: 99%
“…22,37,55,56 Evidence is accumulating that these structural changes help explain the relationship between poverty, chronic stress, and cognitive and behavioral outcomes. 39,43,[46][47][48][49][50][51][52][55][56][57][58] For example, younger adolescents exposed to high cumulative life stress during childhood have been shown to demonstrate poorer executive functioning related to smaller PFC volumes. 56 Similarly, 1 longitudinal study found that the relationship between early-life poverty and conduct disorder symptoms later in life was mediated by volume reductions in the orbitofrontal cortex.…”
Section: Prefrontal Cortex: Executive Functionsmentioning
confidence: 99%
“…However, these short-term benefits are proposed to be associated with long-term functional and structural changes of limbic-related brain regions-perhaps most notably in the amygdala-that manifest as a function of the severity of the ELS exposure (1,9,27,36,37). Consistent with this framework, in childhood, the severity of ELS exposure has been positively associated with amygdala reactivity to both threatening and happy faces in a dose-dependent manner (26,38). Similarly, as adults, the severity of prior stress exposure has also been associated with amygdala engagement in response to threatening faces (19).…”
Section: Happy Amygdala Reactivity Log Oddsmentioning
confidence: 96%
“…Mechanisms by which ELS affects adult psychopathology are thought to involve-at least in part-engagement of the HPA axis in the immediate response to the stressor (2,6,10,11,19,26). This engagement of the HPA axis and release of stress-related hormones are, in turn, believed to cause structural and functional changes in the neural circuits that underlie emotion processing.…”
mentioning
confidence: 99%
“…McCrory, De Brito, & Viding, 2011;E. J. McCrory et al, 2013;Olsavsky et al, 2013;Suzuki et al, 2014;N Tottenham et al, 2011;Van Harmelen et al, 2013) and altered striatal reward processing (Boecker et al, 2014;Dillon et al, 2009;Hanson, Hariri, & Williamson, 2015;Holz et al, 2016;Philip et al, 2016). Furthermore, CM has been associated with altered activity in, as well as functional connectivity between, PFC regions associated with stress response and emotion regulation (Bruce et al, 2013;Gregory A. Fonzo, Huemer, & Etkin, 2016;Jankowski et al, 2016;Lim et al, 2015;Mueller et al, 2010;Vanessa B Puetz et al, 2014;S J A van der Werff et al, 2012;van Harmelen, Hauber, et al, 2014;van Harmelen, van Tol, et al, 2014).…”
Section: Brain Functioningmentioning
confidence: 99%